Genetic polymorphisms in mutagenesis progeny of Arabidopsis thaliana irradiated by carbon-ion beams and γ-rays irradiations. (1st February 2020) - Chen, Xia; Feng, Hui; Du, Yan; Luo, Shanwei; Li, Wenjian; Yu, Lixia; Feng, Zhuo; Cui, Tao; Zhou, Libin
Abstract: Purpose: Heavy-ion beams and γ-rays are popular physical mutagenesis to generate mutations in higher plants. It has been found that they show different mutation frequencies and spectrums of phenotype induction, however, the characteristics of heavy-ion beams on genetic polymorphism have not been clarified by comparing with γ-rays. Materials and methods: In the present study, seeds of Arabidopsis thaliana were exposed to carbon-ion beams (with linear energy transfer (LET) of 50 keV/μm) and γ-rays (with average LET of 0.2 keV/μm) irradiation. By using inter-simple sequence repeat (ISSR) and random amplified polymorphic DNA (RAPD) analysis, the genetic polymorphism of both M1 and M3 plants were investigated, respectively. Results: Carbon-ion beams induced relatively higher polymorphism rate in both M1 and M3 generation than γ-rays: the polymorphism rates of M1 plants derived from carbon-ion beams irradiation are 12.87% (ISSR-C) and 9.01% (RAPD-C), while are 7.67% (ISSR-γ) and 1.45% (RAPD-γ) of plants derived from γ-rays. In M3 generation, the polymorphism rates of ISSR-C, RAPD-C, ISSR-γ, and RAPD-γ are 17.64%, 22.79%, 12.10%, and 2.82%, respectively. Conclusions: In summary, the exposure to carbon-ion beams and γ-rays lead to the change of genomic DNA of A. thaliana, which could be tested in M1 plants and M3 plants by ISSR and RAPD technology. So, both carbon-ion beams and γ-rays can induce variations of genetic polymorphisms in M1 plants and M3 plants. The genetic polymorphisms of M1 plants and M3 plants induced by carbon-ion beams are higher than γ-rays, indicating that heavy-ion beams irradiations mutation breeding is more advantageous than conventional ionizing radiations. Average molecular polymorphism of M1 plants is lower than M3 mutants, by nearly 4.77% (ISSR-C), 13.78% (RAPD-C), 4.43% (ISSR-γ), and 1.37% (RAPD-γ). We hope our study will provide basic information for understanding the effects of carbon-ion beams and γ-rays for plant mutation breeding.